2014
DOI: 10.1037/a0032452
|View full text |Cite
|
Sign up to set email alerts
|

The impact of betrayal trauma on the tendency to trust.

Abstract: Early experiences of violation perpetrated by close others, or betrayal traumas, may interfere with developing social capacities, including the ability to make healthy decisions about whom to trust. Betrayal trauma theory posits that survivors of trauma are at increased risk of making inaccurate trust decisions in interpersonal contexts, thus interfering with intimacy and elevating risk for revictimization. The current study examined the impact of betrayal trauma exposure on trust tendencies using both self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 25 publications
6
74
1
Order By: Relevance
“…Columns (2) and (3), as well as (5) and (6) acknowledge the potential influence of the suggested control variables and individual-level fixed effects. With respect to positive shocks, an initially strong connection to trust levels becomes statistically meaningless when fixed effects on the individual level are accounted for (these results are in line with those from Gobin and Freyd, 2014). From column (1) to (2) alone, the magnitude of the main coefficient of interest decreases by a factor of 2.6, from 0.08 to 0.03.…”
supporting
confidence: 75%
“…Columns (2) and (3), as well as (5) and (6) acknowledge the potential influence of the suggested control variables and individual-level fixed effects. With respect to positive shocks, an initially strong connection to trust levels becomes statistically meaningless when fixed effects on the individual level are accounted for (these results are in line with those from Gobin and Freyd, 2014). From column (1) to (2) alone, the magnitude of the main coefficient of interest decreases by a factor of 2.6, from 0.08 to 0.03.…”
supporting
confidence: 75%
“…In a study among undergraduate students, Gobin and Freyd (2014) found that experiences of trauma involving betrayal were associated with lower levels of self-reported general and relationship-specific trust. Prior research also indicates the particular importance of mistrust to aggressive behavior.…”
mentioning
confidence: 99%
“…Individuals who experience high-betrayal trauma are less likely to trust others (Gobin & Freyd, 2013), and might thus encounter additional challenges in interacting with providers. In this study, previous betrayal trauma was found to predict the quality of the relationship an individual has with his or her medical provider.…”
Section: Discussionmentioning
confidence: 99%